Intensive, Short-Term Presenting With a Science Outreach Program Enhances Positive Science Attitudes and Interest in Lifelong Learning About Science - Sripaoraya, Nantida; Spronken-Smith, Rachel; Longnecker, Nancy (Frontiers in Education, 2022)
This study investigated impacts of intensive, short-term participation as a science outreach presenter on attitudes towards science and interest in lifelong learning about science. Participants included high school and university students who volunteered to assist as presenters over 1 week when Science Caravan—an extensive science outreach program in Thailand, run by the National Science Museum—visited their locality. This study employed mixed methods over two phases. Phase One involved three questionnaires. Two questionnaires were administered to current presenters (N = 690), pre-presenting (before training) and immediately post-presenting at 12 locations of the Science Caravan tour in 2017–2018. A third questionnaire collected data from previous, alumni presenters (n = 726). Phase Two involved interviews with current presenters (n = 19) and alumni presenters (n = 19). While presenters already had positive attitudes towards science, the brief but intensive experience of being a Science Caravan presenter enhanced science attitudes in four scales—with more positive attitudes about Self-concept in science, Value of science to society, and Future participation in science, and decreased Anxiety about science presenting. Participation had a greater impact of reducing anxiety in female presenters compared to male presenters. The experience of presenting with Science Caravan led to the development of more positive attitudes towards science and increased interest in lifelong learning activities regarding science, including presenters’ interest in science-related education. The increased interest in lifelong learning activities was correlated with positive attitudes about and self-efficacy in science. This study provides evidence that a short-term, intensive experience of science outreach can lead to increases in positive attitudes towards science and lifelong learning.